PEDAGOGICAL DIAGNOSIS OF FUTURE TEACHERS IN TEACHING ENGLISH (Multidisciplinary Journal of Science and Technology, 2025)
The article examines current issues of organizing pedagogical practice in the new conditions of work of schools of general and vocational education. Particular attention is paid to diagnostics of students in an educational organization. The work of future English teachers in the process of pedagogical practice is presented.